Service Quality And Consumer Trust As Predictors Of Customer Satisfaction In Sungai Bawang Cultural Village, Muara Badak District, Kutai Kartanegara Regency - Mia Elvina; Sutarto Wijono; Susana Prapunoto (Pusat Publikasi Nusantara, 2025)
This study aims to analyze the influence of service quality and consumer trust on customer satisfaction in Sungai Bawang Cultural Village, Muara Badak District, Kutai Kartanegara Regency. The approach used is quantitative with correlational design and multiple linear regression analysis. Data was collected through a questionnaire distributed to 83 respondents. The results of the analysis show that 58.1% of the variation in consumer satisfaction can be explained by both independent variables. The F test shows that the quality of service and consumer trust simultaneously have a significant effect on consumer satisfaction. The t-test revealed that each independent variable also had a partially significant effect. These findings indicate that improving service quality and consumer trust can increase tourist satisfaction, thereby contributing to the sustainability of Sungai Bawang Cultural Village as a tourism destination. This research is expected to be a reference for tourism village managers in improving services and building trust to maximize the visitor experience.